Acoustic Characteristics of Several Fish Species of Jenggalu River Estuary Through Controlled Measurements in Bengkulu City - Bakhtiar, Deddy; Malau, Defi Dormasi; Silaban, Sintiana; Esra, Gracia; Mayub, Afrizal (PT FORMOSA CENDEKIA GLOBAL, 2024)
Estuary waters are important habitats as spawning and nursery areas for various species of fish so it is necessary to monitor the fish resources in them. The purpose of this study is to analyze the target strength values of various estuary fish species from the Jenggalu River estuary through controlled measurements and formulate the relationship of target strength to total fish length. The controlled acoustic method uses a Simrad EK-15 echosounder with a frequency of 200 kHz. Measurements were taken in the pond using the tethered method, where the dead test fish was hung horizontally on the frame and then the acoustic signal was emitted vertically from above. The samples used were 13 species of fish with a total of 62 fish. The results obtained the average value of target strength has a range of values ranging from -68.86 to -54.80 dB. The relationship between the target strength value and the total length of the fish shows a very strong relationship with the correlation coefficient (r) value ranging from 0.86 – 0.96 and the coefficient of determination shows more than 74% of the TS value is influenced by the size of the fish length. The resulting equation model of the relationship between TS and total length size showed that TS values on the dorsal aspect increased in proportion to the square of fish length.